Comparison of Direct Runoff Hydrographs of Two Ungauged Sub-Basins Using Instantaneous Unit Hydrograph Approach - Hüseyin Akay; Müsteyde Baduna Koçyiğit (Doğal Afetler ve Çevre Dergisi)
The aim of this study is to estimate the direct runoff hydrographs at the outlets of two ungauged sub-basins which have similar drainage areas and elongation ratios. For the analysis, two neighboring sub-basins of Araç Creek located in the Western Black Sea Basin were selected. Drainage networks of the sub-basins were created via ArcGIS and some morphometric parameters were calculated. Unit hydrographs for two sub-basins were estimated using Nash’s instantaneous unit hydrograph method. In order to compare the hydrographs of two sub-basins under similar conditions, hydrologic analysis was performed using the same curve number and precipitation model in HEC-HMS hydrologic model. According to the model results, peak discharges in sub-basin 1 and sub-basin 2 were found to be 18.71 and 27.83 m3/s, respectively, and the peak discharge of sub-basin 2 was found to be 49% higher than that of sub-basin 1. Furthermore, time to peak of the sub-basin 2 was estimated as 5 hours while it was 7 hours for the sub-basin 1. According to the calculated hydrographs, it was concluded that sub-basin 2 was more susceptible to flash floods than sub-basin 1. The adopted method also enables prioritization of the sub-basins according to the flash flood potential. During design stage of hydraulic structures located on rivers without flow measurements, hydrograph and peak flow discharges can be estimated by using this method where properties of the sub-basins can directly be used.